Investigating housing distribution for the expatriate population in Doha - Hatem Ibrahim (18112237) (2019)
Expatriates constitute 89% of Qatar’s total population, and are becoming important factors in the economic dynamism by satisfying employment sectors. The theoretical framework of this paper is based on Gordon’s theory which distinguishes between migrants: housing streams and employment streams. The objectives are to: 1) Investigate housing distribution for the expatriate population based on governmental regulations for the blue-collar, and housing preferences for the white-collar workers and 2) Develop a recommendation for expatriates’ housing distribution in Doha. The research tools are: 1) Content analysis of recent census data, 2) Questionnaire survey for white-collar workers in different sectors, and 3) Interview with real estate experts to present insights about the expatriates housing distribution in Doha. The paper concludes that housing streams in Doha are dynamic, whereas employment streams are static. The governmental approach shows that a qualitative change in the demographic composition for Doha’s population will take place; namely, white-collar workers would gradually replace blue-collar workers in future. Other Information Published in: Urban, Planning and Transport Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/21650020.2019.1635520